Palmer, Washington County - Peters, Grant (Kansas State University, The Chapman Center for Rural Studies, 2012)
This study is of the city of Palmer, located in Washington County, Kansas, and how the entrepreneurial spirit allowed it to flourish. This industry allowed the town to thrive though all manner of trials and disasters. This study shall include maps, pictures, interviews, and publishing.
Grant Peters, “Palmer, Washington County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/109.
Keywords: Washington County; Palmer; E.A. Thomas; Palmer Rural Telephone; Peach Creek; Railroad